Ubuntu, migration, and ministry : being human in a Johannesburg church - Hankela, Elina. (Studies in Systematic Theology, 2014)
Ubuntu, Migration and Ministry invites the reader to rethink ubuntu (Nguni: humanness/humanity) as a moral notion in the context of local communities. The socio-moral patterns that emerge at the crossroads between ethnography and social ethics offer a fresh perspective to what it means to be human in contemporary Johannesburg. The Central Methodist Mission is known for sheltering thousands of migrants and homeless people in the inner city. Based on ethnographic fieldwork, primarily conducted in 2009, Elina Hankela unpacks the church leader's liberationist vision of humanity and analyses the tension between the congregation and the migrants, linked to the refugee ministry. While relational virtues mark the community's moral code, various regulating rules and structures shape the actual relationships at the church. Here ubuntu challenges and is challenged. Winner of the 2014 Donner Institute Prize for Outstanding Research into Religion.